ISOLASI DAN KARAKTERISASI SENYAWA TERPENOID DARI DAUN Macaranga beccariana Merr. - Doni Prio Atmoko; Eva Marliana; Erwin Erwin (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2018)
Isolation and characterization of terpenoid compounds from ethyl acetate fraction of Macaranga beccariana Merr. have been done. The separation process at ethyl acetate fraction using gravity column chromatography with gradient elution method. The obtained isolates were tested for purity using thin layer chromatography with various eluents namely n-hexane, chloroform, methanol, acetone and ethyl acetate with Rf values 0; 0.75; 0.80; 0.87 and 0.97 respectively. The terpenoids which were successfully isolated were white crystals with a mass of 0.0119 grams. UV analysis produced 1 peak at l 207.03 nm. Analysis of compounds with FT-IR indicated the functional groups O-H, aliphatic C-H, aliphatic C=C, C-O and C=O. Based on the results of the UV and FT-IR spectrum, the isolate compounds were thought to contain terpenoids.